The effect of contrast agents on dose calculation in conformal radiotherapy planning using computed tomography for tumors at different anatomical regions - Yabsantia, S.; Tangboonduangjit, P.; Tannanonta, C. (Journal of Thai Association of Radiation Oncology, 2010)
The purpose of this study was to evaluate the effect of contrast agents on dose calculation in 3-Dimensional Conformal Radiotherapy (3D-CRT) for brain, thorax and upper abdomen region in Ramathibodi hospital. Five, six and four cancer patients for brain, thorax and upper abdomen region respectively were studied for retrospective study. Each patient took two sets of CT images in the same position before and after IV contrast agent injection. To avoid the movement artifact, the CT images of thorax and upper abdomen regions of without-contrast agent were imitated by overriding the density to the organs or regions using the density obtained from the original without-contrast agent CT images. The approved plan by a radiation oncologist was copied to both with- and without-contrast agent CT images. Both of the plans used the same monitor unit. The doses calculated from two plans were compared with regard to tumor volume and organs at risk volume. The paired sample t-test and gamma evaluation were used to evaluate the differences in dose distributions between two plans. The results of doses of tumor volume and organs at risk volume were not signifi cantly different between with - and without-contrast agent CT images for brain, thorax and upper abdomen region (p > 0.05), except heart organ in thorax region (p < 0.05) but the dose differences were less than 1% compared to dose calculated from without-contrast agent CT images. The number of passed pixel was more than 95% and the gamma value was less than 0.5 for dose distributions compared between two sets of CT images. As a result, using contrast agent at the time of CT simulation dose not signifi cantly affect on dose calculation in 3D-CRT.